Electrolytes at interfaces - Durand-Vidal, S. (Progress in theoretical chemistry and physics ;, 2000)
The aim of this book is to provide the reader with a modern presentation of ionic solutions at interfaces, for physical chemists, chemists and theoretically oriented experimentalists in this field. The discussion is mainly on the structural and thermodynamic properties, in relation to presently available statistical mechanical models. Some dynamic properties are also presented, at a more phenomenological level. The initial chapters are devoted to the presentation of some basic concepts for bulk properties: hydrodynamic interactions, electrostatics, van der Waals forces and thermodynamics of ionic solutions in the framework of a particular model: the mean spherical approximation (MSA). Specific features of interfaces are then discussed: experimental techniques such as in-situ X-ray diffraction, STM and AFM microscopy are described. Ions at liquid/air, liquid/metal and liquid/liquid interfaces are considered from the experimental and theoretical viewpoint. Lastly some dynamic (transport) properties are included, namely the self-diffusion and conductance of small colloids (polyelectrolytes and micelles) and the kinetics of solute transfer at free liquid/liquid interfaces.